Identification of Types and Abundance of Solid Waste in Pangkalan Jambi Village, Bengkalis Regency - Ayu Septiani; Aras Mulyadi; Bintal Amin (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) Universitas Riau, 2023)
Various human activities fulfill their welfare by producing food, drinks, and other goods which in turn can generate solid waste and liquid waste. Solid waste often contaminates residential areas, coastal mangroves, and the aquatic environment. In addition, the mangrove coast which is used as a tourist area can also receive solid waste as a result of local activities. This study aims to identify the type and abundance of solid waste in Pangkalan Jambi Village, Bengkalis Regency. This research was conducted in Pangkalan Jambi Village, Bukit Batu District, Bengkalis Regency. The method in this study is a survey method. Sampling technique using the quadrant transects method, each station was drawn as many as 5 transect, and each transect consisted of 5 plots with a quadrant plot size of 5 x 5 m2. The data analyzed included identifying the amount of solid waste, calculating the abundance of solid waste, analyzing the differences in the type and abundance of solid waste between stations, and measuring environmental parameters. The results showed that the highest abundance of solid waste was obtained during the weekend at 3.15 units/m2. The second highest was before the weekend at 2.53 units/m2, and the lowest solid waste was obtained during the weekend at 2.36 units/m2. Meanwhile, the highest weight of solid waste was found in the tourist area of the Mangrove Education Center (MEC), the second highest came from the community settlements of Pangkalan Jambi Village and the lowest was in the Mangrove Area of Pangkalan Jambi Village. The types of solid waste at the research location are plastic, metal, glass, rubber, wood, cloth, and others.